NOTE ON THE FAUNA OF DROSOPHILA (DIPTERA: DROSOPHILIDAE) AND THE FIRST RECORD OF OPOMYZA FLORUM (DIPTERA: OPOMYZIDAE) FROM MT. GOČ, SERBIA (Acta Entomologica Serbica, 2012)
Fauna of Drosophilidae in Serbia has been studied for 40 years. This paper presents the results of faunistic research conducted on Mt. Goč in June 2011 in two forests (beech and oak), which are significantly different in the type of vegetation and microclimatic factors. In the oak forest eight species of Drosophila were registered, while in the beech forest only five species were recorded. A relatively small number of species recorded is, among other things, the result of extremely bad weather conditions during the collection attempts. An interesting non-drosophilid fly was also found in the sample - Opomyza florum Fabricius, 1794 (Diptera: Opomyzidae). Since there is very little data concerning the distribution of O. florum in Serbia, this paper is an invitation to entomologists to further study this species, including faunistical, ecological and behavioral aspects, keeping in mind its potential economic impact